PENGARUH KEWAJARAN HARGA, KUALITAS PRODUK TERHADAP MINAT BELI MELALUI SUASANA TOKO PADA UD. MAKMUR LAMONGAN - Nawari Nawari (LPPM UNISDA, 2023)
This research determine the effect of price fairness and product quality moderated by store atmosphere on consumer buying interest. What is in the UD. Makmur Sukodadi Lamongan The number of samples determined was 80 respondents using purposive sampling method. As an independent variable, namely the reasonableness of price and product quality, and the moderating variable is the atmosphere of the store, while the dependent variable is consumer buying interest. The analysis used includes validity test, reliability test, classical assumption test, Moderated Regression Analysis (MRA) and hypothesis testing. The results of the analysis using moderated regression analysis can be seen that the variables of price fairness and product quality have a positive effect on consumer buying interest, and the store atmosphere variable moderates the reasonableness of prices on consumer buying interest, and the store atmosphere variable successfully moderates product quality on consumer buying interest. The results of the analysis using the coefficient of determination show that 94.9 percent of the variation in consumer buying interest can be explained by the independent variables and moderating variables studied in this study and 5.1 percent is explained by other factors outside the model.